2005
DOI: 10.1038/sj.onc.1208811
|View full text |Cite
|
Sign up to set email alerts
|

Promoter CpG hypomethylation and transcription factor EGR1 hyperactivate heparanase expression in bladder cancer

Abstract: Heparanase plays a critical role in the degradation of extracellular matrix and cell membrane and is frequently upregulated in malignant tumors. Transcription factor, early growth response 1 (EGR1), is closely associated with inducible transcription of the heparanase gene. We hypothesized that promoter CpG hypomethylation with increased EGR1 expression could determine heparanase expression during the pathogenesis of bladder cancer. Bladder cancer cell lines (J82, T24 and transitional cell carcinoma) significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…Reportedly, inducible transcription of human heparanase gene is mediated by activation of early growth response-1 (Egr-1) transcription factor in activated T cells. 29) Ogishima et al 30) reported that increased heparanase expression in prostate cancer tissues results from up-regulation of Egr-1. In addition, Egr-1 is reportedly overexpressed in hypertrophied hearts of mice treated with chronic ISO treatment, 31) and Egr-1 deficient mice revealed a blunted ISO-induced hypertrophy response.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, inducible transcription of human heparanase gene is mediated by activation of early growth response-1 (Egr-1) transcription factor in activated T cells. 29) Ogishima et al 30) reported that increased heparanase expression in prostate cancer tissues results from up-regulation of Egr-1. In addition, Egr-1 is reportedly overexpressed in hypertrophied hearts of mice treated with chronic ISO treatment, 31) and Egr-1 deficient mice revealed a blunted ISO-induced hypertrophy response.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies using knockdown strategies have confirmed a central in vivo role for EGR1 in tumor angiogenesis, growth, and metastasis in breast adenocarcinoma (47,51) and tumor progression in prostate adenocarcinomas (52,53). A recent study of human prostate cancer samples has shown a correlation between EGR1 expression and HPSE mRNA expression (39), further supporting a role for EGR1 in regulating HPSE transcription in tumor cells. In this article we have functionally dissected the human HPSE promoter and identified EGR1 as critical in binding to two elements in the HPSE promoter and regulating transcription in tumor cells.…”
mentioning
confidence: 89%
“…Jiang et al (37) also showed there were three functional Sp1 sites in the promoter that acted cooperatively with the ETS family member, GABP. At the endogenous gene level, it has been shown that methylation of a CpG region in the HPSE promoter can contribute to the silencing of the gene (21,38,39) and more recently, the expression of a dominant negative form of cAMP-response element-binding protein was shown to decrease HPSE mRNA levels in melanoma cells (40).…”
mentioning
confidence: 99%
“…Several studies have shown that the epigenetic changes that occur in cancer include not only promoter CpG island hypermethylation and silencing of tumor suppressor genes (Herman and Baylin, 2003), but also promoter CpG island hypomethylation (Feinberg and Vogelstein, 1983;Kaneda et al, 2004). Such promoter hypomethylations in different cancers were associated with upregulated expression of tumor promoting genes such as BCL2 (Hanada et al, 1993), MDR1 (Nakayama et al, 1998), HOX11 (Watt et al, 2000), MYC, c-Ha-RAS, c-FOS and ALPHA FETOPROTEIN (Fang and Xiao, 2001), MASPIN (Ogasawara et al, 2004), MEL1S (Yoshida et al, 2004), EGR1 that upregulates expression of heparanase (Ogishima et al, 2005), SYNUCLEIN GAMMA (Gupta et al, 2003;Liu et al, 2005) and some other genes (Sato et al, 2003). Exogenously added estrogen or tamoxifen can induce promoter hypomethylation of PAX2 , and treatment with chemotherapeutic compounds can induce Histone-H3 acetylation and Histone-H3 lysine-4 methylation at the MDR1 promoter (Baker et al, 2005) that result in upregulation of these tumor promoting genes.…”
Section: Differentiation Plasticity In Normal and Cancer Stem Cells Jmentioning
confidence: 99%